2021
DOI: 10.1016/j.cels.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Cell states beyond transcriptomics: Integrating structural organization and gene expression in hiPSC-derived cardiomyocytes

Abstract: Highlights d Automated image-based classification of subcellular organization in single cells d Integrated analysis of gene expression and cell structure to classify cell state d Curated dataset containing over 30,000 hiPSC-derived cardiomyocytes d Open-source images, analysis code, and quantitative tools

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 100 publications
2
36
0
Order By: Relevance
“…Notably, this analysis revealed that gene sets as small as two to twelve genes enabled prediction of time point with high accuracy, similar to the accuracy achieved by using over 1000 of the most highly variable genes. These data indicate that a small subset of carefully-chosen gene targets may be informative for downstream studies where gene set size is limited, such as in functional knock-out assays, in vivo experiments, or image-based RNA FISH studies 71 . In summary, we used scRNA-seq to profile gene expression in cardiomyocytes and non-cardiomyocytes during cardiomyocyte differentiation and extended culture in vitro.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Notably, this analysis revealed that gene sets as small as two to twelve genes enabled prediction of time point with high accuracy, similar to the accuracy achieved by using over 1000 of the most highly variable genes. These data indicate that a small subset of carefully-chosen gene targets may be informative for downstream studies where gene set size is limited, such as in functional knock-out assays, in vivo experiments, or image-based RNA FISH studies 71 . In summary, we used scRNA-seq to profile gene expression in cardiomyocytes and non-cardiomyocytes during cardiomyocyte differentiation and extended culture in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…Two differentiation protocols were used, referred to as “Protocol 1” and “Protocol 2” in the text. Protocol 1 is based on a previously reported small molecule differentiation method with modifications 75 , 76 as described in Gerbin et al 71 . HiPSC cultures were dissociated into single cells using Accutase and plated into matrigel-coated 6 well-plates at 125–350 k cells per well in mTeSR1 supplemented with 1% P/S and 10 µM Rock Inhibitor (Day -3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the rapid development of ST technologies, it is now possible to perform both transcriptomic profiling and morphology analyses for the same cells, thereby providing a great opportunity to systematically investigate the relationship between these two fundamentally different approaches. A few methods have recently been developed that focus on integration of both modalities (He et al 2020;Tan et al 2020;Gerbin et al 2021). Although not directly related to spatial transcriptomics, an interesting finding from living imaging analysis indicates that changes in morphology might even predict cell fate or state before this can be observed in the transcriptomic output (Buggenthin et al 2017).…”
Section: Discussionmentioning
confidence: 99%